2020
DOI: 10.1080/10255842.2020.1793965
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of joint contact pressure in the index finger using a hybrid finite element musculoskeletal approach

Abstract: The knowledge of local stress distribution in hand joints is crucial to understand injuries and osteoarthritis occurrence. However, determining cartilage contact stresses remains a challenge, requiring numerical models including both accurate anatomical components and realistic tendon force actuation. Contact forces in finger joints have frequently been calculated but little data is available on joint contact pressures. This study aimed to develop and assess a hybrid biomechanical model of the index finger to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…Joint contact pressure levels estimated by the finite element model ranged between 2 and 8 MPa which is consistent with the findings of Faudot et al [14]. The largest effect of fusion angle on adjacent loading was observed for participant P4, especially for PIP where the difference in joint contact pressure between control condition and a fusion of 0° is 1.9 MPa (Fig.…”
Section: Arthrodesis Effect On Adjacent Joint Contact Pressuressupporting
confidence: 90%
See 4 more Smart Citations
“…Joint contact pressure levels estimated by the finite element model ranged between 2 and 8 MPa which is consistent with the findings of Faudot et al [14]. The largest effect of fusion angle on adjacent loading was observed for participant P4, especially for PIP where the difference in joint contact pressure between control condition and a fusion of 0° is 1.9 MPa (Fig.…”
Section: Arthrodesis Effect On Adjacent Joint Contact Pressuressupporting
confidence: 90%
“…This result is not surprising as this participant also showed the largest variations of finger posture and muscle force. It confirms results from previous studies showing an intricate link between abilities (applied force and finger posture), muscle forces, and joint loading [14,17] and justifying the need for more studies to understand the outcomes of such surgical acts. By combining all these measurements and results, this study showed that arthrodesis simulation can lead to participant specific adaptations of index finger posture, inducing an increase in muscle forces ultimately resulting in higher contact pressure on the joint's cartilage.…”
Section: Arthrodesis Effect On Adjacent Joint Contact Pressuressupporting
confidence: 87%
See 3 more Smart Citations